Seguimento de recém-nascidos egressos de unidade de terapia intensiva neonatal na perspectiva da integralidade da atenção à saúde - Carvalho, Alciléa Leite de (2013)
In Brazil, the Ministry of Health, through the Secretariat of Attention to Health Care advocates the accompaniment of new born babies at risk and at high risk through the outpatient follow up clinics, as well as through basic care programs. The dialogue between these services and prenatal care is undisputedly relevant, when founded on the principles of care, those being quality and integrality. In light of this, the study aims at understanding aspects of integrality of the care given to newborns leaving neonatal intensive care units of the health care service network in Fortaleza. The study is supported by the perception of the health care staff members in the neonatal follow-up clinics. It is a qualitative case study in which six doctors were the subjects. These doctors work in four follow-up clinics in Fortaleza. Semi-structured individual interviews were used and the information collected was analyzed according to the content analysis technique. The results have been presented in three main categories: a) Factors facilitating the mother’s understanding concerning the reasons for follow up; b) the daily work of the clinics and c) the perception of the doctors regarding the follow-up care which is offered. It was found that the mother’s understanding of the motive for follow-up visits is related to the information given to the family during hospitalization and to the approach taken during the follow-up appointments. The tie established between the doctor and the family was mentioned as a facilitator to follow-up as well as the mother’s understanding of it. It was also found that the doctors’ individual initiatives were essential in overcoming the structural obstacles for follow-up visits in cases of greater complexity. In these cases accountability is a determining factor to ensure transportation to the clinic. This reveals the fragility of the service structures under study. There are problems with an open schedule which would allow mothers to have free access to the clinic. At the same time, mothers requesting services at unscheduled times was frequently mentioned. Thus, the availability of a follow-up team as part of the clinic’s structure was pointed out as a facilitator for care giving. Sharing follow-up activities with the Strategic Family Health program is recognized as necessary, however the institutional mechanisms of communication between the two levels of health care are non-existent. Thus this lack, as well as other aspects, results in the mothers and/or relatives being the main interlocutors of this process. In the study, the lack of confidence in the continuity of the care outside the clinic’s structure was evident. The doctors who were interviewed have perceived an improvement in the quality of care offered during recent years.